(untitled) (Psychology Travelogs, 2024)
The article undertakes a theoretical examination of the psychological conditions influencing the image of a cadet unit commander. It is revealed that the image of the cadet unit commander reflects the officer’s skills, knowledge, competence, as well as the values guiding their professional activities. The criteria for selecting models of the commander’s behavior are analyzed, namely: the behavior model must align with the goals of the military organization and the officer; comply with laws and norms accepted in society; embody moral impeccability; be adaptable to complex situations; and include a self-critical evaluation of one’s behavior model. The article defines the place and role of the image in the process of managing a military team. A group of internal and external conditions is identified, representing a combination of psychological and socio-psychological factors. The psychological features of the commander’s image are outlined: proximity to genuinely professionally significant qualities of the unit commander; limitations on the impact of the image within the framework of the target (professional) group united by common activities; conformity of the image with the nature of military activities, expectations, and traditions accepted in the military environment; constraints on choosing alternative, "non-typical" behavioral models for a military leader; diverse perceptions of the role and position of the unit commander among different categories of military personnel; dependence of the unit commander’s image on the results of the unit’s service and combat activities; alignment with established legal, social norms, and rules of military etiquette. The prospects for further development of effective psychological approaches to shaping the image of the unit commander are outlined.